Centralizm demokratyczny w gospodarce socjalistycznej - Poliński, Romuald (Wydział Prawa i Administracji UAM, 1975)
In the conclusion the author has stated that the democratic centralism means the optimal extent of central planning, the prolongation of planning horizon and the proper relationship between the short and long term planning.
Democratic Centralism in the Socialist Economy